2012
DOI: 10.1097/jcp.0b013e31825ac35c
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of 27 Annotated Genes for Clozapine Pharmacogenetics

Abstract: We could not convincingly replicate most of the previous studies, a result that is possibly due to modest association between the suggested genes. Rather, we found a new candidate gene, ABCB1, for treatment response, which may provide a hypothesis on the relationship between the blood-brain distribution of CLZ and its clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 62 publications
3
37
0
1
Order By: Relevance
“…CYP1A2*1F polymorphisms were associated with a super-refractory schizophrenia group of patients, compared to controls, thus replicating previous work, and identifying this polymorphism as a moderator of clozapine response 50. However, as is the case in clozapine pharmacodynamic pharmacogenetic research, other studies have not replicated these findings in relation to CYP1A2 polymorphism and clozapine response 51,52. Ethnic variation between the study populations has been suggested as a cause of this, with there being a higher frequency of the CYP1A2*1F allele in those of European ancestry 27…”
Section: Pharmacogenomics and Clozapine Responsesupporting
confidence: 72%
“…CYP1A2*1F polymorphisms were associated with a super-refractory schizophrenia group of patients, compared to controls, thus replicating previous work, and identifying this polymorphism as a moderator of clozapine response 50. However, as is the case in clozapine pharmacodynamic pharmacogenetic research, other studies have not replicated these findings in relation to CYP1A2 polymorphism and clozapine response 51,52. Ethnic variation between the study populations has been suggested as a cause of this, with there being a higher frequency of the CYP1A2*1F allele in those of European ancestry 27…”
Section: Pharmacogenomics and Clozapine Responsesupporting
confidence: 72%
“…Despite the important function of rs2069522, its association with breast cancer risk has not been clearly demonstrated. Genetic studies have only shown that it had the potential to affect colorectal cancer risk and the treatment response to clozapine in schizophrenic patients among British Caucasians and Koreans, respectively [41,42]. However, those results were not significant after correction for multiple testing.…”
Section: Discussionmentioning
confidence: 99%
“…A good example of inconsistent replication result of genetic associations is the atypical antipsychotic clozapine with its complex pharmacological effects via the dopaminergic, serotonergic, adrenergic, and histaminergic receptors within the central nervous system. Over the years, conflicting study results exist in the literature for association between clozapine response with either SNPs of each known pharmacological receptor subtype [1013], combinations of polymorphisms [14], and metabolizing enzymes and transporters [15]. It is also of note that the original association regarding combination of polymorphisms was not replicated in a subsequent study [16].…”
Section: Scientific Challenges and Complexitymentioning
confidence: 99%
“…It is also of note that the original association regarding combination of polymorphisms was not replicated in a subsequent study [16]. The recent identification of yet another new candidate gene for clozapine treatment response [15] illustrates the limitation of candidate gene approach in that there is always the possibility of involvement of other yet-to-be-identified genes, including those that have not been known to be linked to the pharmacology of the drug, that could account for additional variability in patient's therapeutic response. More importantly, the effect size of most genetic variants is small to modest.…”
Section: Scientific Challenges and Complexitymentioning
confidence: 99%
See 1 more Smart Citation